THE TRENDS IN BED OCCUPANCY RATE (BOR) AT SITI AISYAH ISLAMIC HOSPITAL MADIUN 2022-2024: A CRITICAL ANALYSIS OF HOSPITAL SERVICE EFFICIENCY - Offia Melda Permata Hartamto; Sholihul Absor; Heru Suswojo (Global Journal of Health Administration, 2025)
Objective: This study aims to analyze the BOR trend at Siti Aisyah Islamic Hospital Madiun from 2022 to 2024, compare it with international benchmarks and theoretical standards such as the Barber Johnson theory, and identify internal factors contributing to suboptimal BOR levels. Methods: This research employed a descriptive quantitative approach using secondary data from internal hospital reports over a three-year period. Results: BOR values showed a progressive increase: 65.24% in 2022, 66.33% in 2023, and 69.00% in 2024. However, they remained below the Barber Johnson efficiency standard range of 75–85%. Various influencing factors were identified, including nursing service quality, inadequate promotion strategies, and inefficient bed management. Conclusion: Although an upward trend is evident, BOR at Siti Aisyah Islamic Hospital remains below the ideal level. Strategic interventions are needed to improve inpatient service efficiency.